The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.jhealeco.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Physician division of labor and patient selection for outpatient procedures

Abstract: Little is known about the ability of incentives to influence decisions by physicians regarding choices of settings for care delivery. In the context of outpatient procedural care, the emergence of freestanding ambulatory surgery centers (ASCs) as alternatives to hospital-based outpatient departments (HOPDs) creates a unique opportunity to study this question. We advance a model where physicians' division of labor between ASCs and HOPDs affects the medical complexity of patients treated in low-acuity settings (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…Specific CPT code indicators are not used because of potential upcoding or differences in coding by provider. 14 Using this sample of physicians is consistent with findings from David and Neuman (2011), whose results suggested that physicians who split patients between ASCs and hospital outpatient departments were observed to sort their more severe cases to hospitals and their less severe cases to ASCs. 15 While other contracts between facilities and physicians may exist, they are unobservable to the researcher.…”
Section: Patient Case Complexitysupporting
confidence: 80%
See 2 more Smart Citations
“…Specific CPT code indicators are not used because of potential upcoding or differences in coding by provider. 14 Using this sample of physicians is consistent with findings from David and Neuman (2011), whose results suggested that physicians who split patients between ASCs and hospital outpatient departments were observed to sort their more severe cases to hospitals and their less severe cases to ASCs. 15 While other contracts between facilities and physicians may exist, they are unobservable to the researcher.…”
Section: Patient Case Complexitysupporting
confidence: 80%
“…7 There are several mechanisms through 5 Winter (2003) has shown that ASCs treat less complex and less costly cases than hospitals. However, David and Neuman (2011) find that physicians who largely refer patients to ASCs treat more medically complex cases than physicians who refer to both hospital outpatient departments and ASCs. 6 Throughout this paper, hospital outpatient departments are referred to as hospitals.…”
Section: Conceptual Frameworkmentioning
confidence: 88%
See 1 more Smart Citation
“…Also, higher population in a patient's zip code is correlated with a lower likelihood of traveling further. This result echos repeated findings in the healthcare literature (see for example Gaynor and Vogt [2003], David and Neuman [2011], Capps, Dranove and Lindrooth [2010], and Town and Vistnes [2001]) that distance matters to healthcare consumers. 15 As well as across insurance types, see analogous results for private patients with and without fixed effects in the appendix and tables A.VI, A.VII and A.VIII.…”
Section: V(i) Multinomial Logit Resultssupporting
confidence: 89%
“…Also, higher population in a patient's zip code is correlated with a lower likelihood of traveling further. This result echos repeated findings in the healthcare literature (see for example Gaynor and Vogt [], David and Neuman [], Capps, Dranove and Lindrooth [], and Town and Vistnes []) that distance matters to healthcare consumers.…”
Section: Estimation Resultssupporting
confidence: 88%